Properties of composite positive continuous functions in $\mathbb{C}^n$ - Bandura, A.I. (Carpathian Mathematical Publications, 2015)
The properties of positive continuous functions with $Q^n_{b}$ and $Q$ are investigated. We prove that some composite functions with $Q$ belong to class $Q^n_{b}.$ A relation between functions with these classes are established.